Descriptive Analysis of Code-Mixing Types Used By Youngsters In Online Communication - Dara Yusnida; Ida Muliawati; Heva Seri Rezeki (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
Online communication through social media platforms has been mushroomed with billions of users is engaging with the devices to show their existence. The tendency to use more than one language while communicating through online sites is greatly noticed among youngster users. To fill the gap from previous studies, the recent research was aimed at investigating kinds of code-mixing used on social media and the factors behind the phenomena among Acehnese youngsters. Descriptive qualitative method was magnified in which the data was collected from the documentation of respondents' older statuses, captions, and comments on Instagram (IG) and WhatsApp (WA). Fifty respondents were selected by using purposive sampling tied up by several criteria: Acehnese native, bi/multilingual, having WhatsApp and Instagram account, and adolescent aged (18-21 years old). A set of mixed questionnaires was also applied to all respondents to investigate the factor or reasons behind the code-mixing usage. The result reveals that phrase level is the dominant code-mixing level used among those youngsters (30%). Phrase level is as a group of words that stand together as a grammatical unit without subject and verb. From the result of the research, it was revealed that those phrase levels were inserted by the Acehnese youngsters within a sentence. On contrary, none of the samples used idiom level (0%) on their social media. For the type of code-mixing which used on the platforms, the form of phonetic typing turns to be the most dominant one. Based on the questionnaire result, being able to learn and understand new words is the biggest reason behind the use of code-mixing among the samples on the online communication networking.